Competitiveness of Indonesian CPO, its successful penetration in the European Union vegetable Oils market, and protectionism trade policies in the EU market to stop it grow further - Loso Judijanto (Cogent Social Sciences)
This study aims to identify a comprehensive conceptual framework and outline the success of specific strategies in these three aspects. This research method uses a systematic literature review research approach guided by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). The article search process is tailored to research topics in journals, scientific articles, and proceedings in the 2017-2023 range. The data extraction process in this study focuses on the Supply Chain Resilience Strategy on aspects of risk mitigation, increased visibility, and collaboration between supply chain partners. Extraction was carried out on 30 articles that were identified according to the criteria. By extracting data, researchers can map the dominant and significant factors from the article search results. The results show that Indonesia’s CPO strategy in the EU market includes, Indonesia conducts economic diplomacy to protect the Indonesian economy, the application of Information Technology (IT) to supply chain partners, recommending sustainable palm oil cultivation, and the last strategy is the implementation of Indonesia Sustainable Palm Oil (ISPO). The results of this study can be used as a reference in further similar research.